Coping With COVID-19: Emergency Stress, Secondary Trauma and Self-Efficacy in Healthcare and Emergency Workers in Italy - Vagni, Monia; Maiorano, Tiziana; Giostra, Valeria; Pajardi, Daniela (Frontiers in Psychology, 2020)
Coping with the coronavirus disease (COVID-19) is a significant risk factor for the psychological distress of health workers. Hence, this study explores the relationship between coping strategies used by health and emergency workers in Italy to manage the stress factors related to the COVID-19 emergency, which may result in the risk of developing secondary trauma. We study differences between healthcare (n = 121) and emergency workers (n = 89) in terms of their coping strategies, emergency stress, and secondary trauma, as well as the relationships of these differences to demographic variables and other stress factors (Instructions and Equipment). For this purpose, we collected data from participants through the following questionnaires online: Secondary Traumatic Stress Scale – Italian Version, The Coping Self-Efficacy Scale – Short Form, an original questionnaire on stressors, and the Emergency Stress Questionnaire (to assess organizational–relational, physical, inefficacy decisional, emotional, cognitive, and COVID-19 stress). We performed a t-test, correlational analysis, and hierarchical regression. The analyses reveal that compared with the emergency worker group, the health worker group has greater levels of emergency stress and arousal and is more willing to use problem-focused coping. Healthcare workers involved in the treatment of COVID-19 are exposed to a large degree of stress and could experience secondary trauma; hence, it is essential to plan prevention strategies for future pandemic situations. Moreover, individual efficacy in stopping negative emotions and thoughts could be a protective strategy against stress and secondary trauma.